A medieval castle - Macdonald, Fiona; Bergin, Mark (New York : Peter Bedrick Books, 1990)
Text and cutaway illustrations depict how people lived and worked inside a medieval castle.
Includes index.
Wilson's Junior High School.
Elem. School Library Collection.
School Library Journal.
6.6
5-8
Keywords: Castles -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Castles; Civilization, Medieval; Castles; Medieval civilization; Castles; Civilization, Medieval